2019
DOI: 10.1111/jonm.12770
|View full text |Cite
|
Sign up to set email alerts
|

The nurse manager’s role in perioperative settings: An integrative literature review

Abstract: Aim To describe the nurse manager's role in perioperative settings. Background The nurse manager's role is complex and its content unclear. Research in this area is scarce. We need to better understand what this role is to support the nurse manager's work and decision‐making with information systems. Evaluation An integrative literature review was conducted in May 2018. Databases CINAHL, Cochrane, PubMed and Web of Science were used together with a manual search. The review followed a framework especially desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Nurse managers also described various challenges in their current work environment, including (among others) fragmented and uncontrolled workloads, and lack of a clear job description, similarly, than previous findings (Bjerregård Madsen et al, 2016; Adriaenssens, Hamelink and Bogaert, 2017; Siirala et al, 2019). They expressed high expectations of administrative support services to ease their workload, and hopes for more real‐time information to assist daily tasks, as also previously reported (Peltonen et al., 2018).…”
Section: Discussionsupporting
confidence: 58%
“…Nurse managers also described various challenges in their current work environment, including (among others) fragmented and uncontrolled workloads, and lack of a clear job description, similarly, than previous findings (Bjerregård Madsen et al, 2016; Adriaenssens, Hamelink and Bogaert, 2017; Siirala et al, 2019). They expressed high expectations of administrative support services to ease their workload, and hopes for more real‐time information to assist daily tasks, as also previously reported (Peltonen et al., 2018).…”
Section: Discussionsupporting
confidence: 58%
“…The system must support the daily unit operations with realtime information. 1 There are several factors involved: patient care processes, surgical procedures, human resources, and physical resources, which are closely related to the key areas that nurse managers focus on in the daily operation of the unit. 23 It is all about staffing, ensuring adequate staffing, rescheduling surgical procedures, confirming physical resources, and tracking daily unit operations.…”
Section: Daily Unit Operations Managementmentioning
confidence: 99%
“…Perioperative nurse managers are responsible for leading and managing the operating room at the operational and tactical levels. 1 According to recent research, perioperative nurse managers oversee areas of practice in the perioperative environment that are beneficial to the safe care of surgical patients and a means to improve efficiency and reduce costs. 2,3 As patient demand for healthcare increases, the number of healthcare professionals decreases and the cost of care increases, the development of perioperative nursing is essential for patient access to healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that nurse managers play a key role in the establishment of a healthy workplace, the recruitment and retention of clinical nurses, and improvements in the quality of care and patient safety [ 10 , 11 ]. As the main body of nursing management, nurse managers are required to master higher levels of education and experience compared with other nurses [ 12 ]. Tertiary general hospitals are associated with the highest healthcare-delivery competence [ 13 ], so nurse managers of tertiary general hospitals are expected to be more proficient in both skills and tasks compared with those of second-tier hospitals.…”
Section: Introductionmentioning
confidence: 99%